Simulations in Medicine. Computer-aided diagnostics and therapy - Roterman-Konieczna, Irena (De Gruyter, 2020)
This book describes application fields of high tech in diagnostics and therapy allowing individual therapy, interpretation of large data bases in form of neuronal signals, help visualization of organs during surgery, robotic surgery, 3D-printing and 3D-bioprinting, augmented reality. It also covers hospital organization including hybrid surgery rooms and personal data flow.